Consumer Protections in Digital Transactions: A Study of Indonesian E-commerce through Positive and Islamic Law - Ris Malasari; Muhammad Darwis; Zainal Said (Sekolah Tinggi Agama islam Negeri Majene, 2026)
The rapid growth of e-commerce in Indonesia has triggered a corresponding increase in consumer protection issues, which is an urgent problem that this study seeks to examine. This study aims to uncover the practice of consumer protection that occurred in Indonesia within the implementation of e-commerce transactions, which is then analysed using the perspective of positive and Islamic laws. Using a normative-empirical legal approach, the study evaluates the compatibility of practices with Sharia principles. We employed a normative-empirical analysis to evaluate e-commerce transactions in Indonesia through the dual lenses of Sheikh Wahbah al-Zuhaili’s fiqh muamalah and the law concerning Consumer Protection (UUPK). Empirical findings show that businesses have limited legal literacy and ethical awareness, often delegating consumer protection responsibilities to platforms and failing to enforce the rights guaranteed by the Consumer Protection Law (UUPK), as seen in widespread issues related to misleading product representations and inadequate dispute resolution mechanisms. Nevertheless, government oversight and formal dispute resolution mechanisms, such as the Consumer Dispute Resolution Agency, are inadequate for the scale and complexity of the digital market. Normatively, this study combines these findings with Sheikh Wahbah al-Zuhaili's Islamic legal framework, showing that common digital practices, such as non-transparent product descriptions and hidden fees, violate the basic pillars of contracts and introduce the prohibited elements of gharar (uncertainty) and tadlīs (deception), thereby rendering transactions invalid under Islam. The study underlines that the ethical principles of fiqh muamalah (trust, justice, and honesty) align with the objectives of the UUPK, together forming a coherent basis for reform. To bridge the current gap, an integrated regulatory approach is essential, combining enhanced law enforcement, business ethics education, and the development of a transparent, Sharia-compliant digital system for online verification and dispute resolution.